PROCESS IMPROVEMENT TO REDUCE WASTE IN THE BIGGEST INSTANT NOODLE MANUFACTURING COMPANY IN SOUTH EAST ASIA - Tannady, Hendy (Journal of Applied Engineering Science, 2019)
This research was conducted at the biggest instant noodle manufacturing company in South East Asia. In the process of producing instant noodle, there is inability to reach the target number of production, this is due to quality factor and waste in the use of raw material. Research uses lean six sigma method. In the define phase, the process of identification of waste is carried out by making VSM and WAM to find out the dominant waste. At the measure phase, the CTQ is decided and calculates the sigma level. In the analyze phase, analysis is done by using VALSAT, determining the type of dominant defect through the Pareto diagram and knowing the causes of defects with fishbone diagram. In the improve phase, improvement is made based on the highest RPN value that is known through the FMEA method. At the control phase, the handle process is carried out so that repairs are carried out continuously. The research finds the highest waste weight is due to defective products of 25.03%, sigma value of 4.75, and activities that gives value added (VA) had the highest percentage of 71.31%. The conclusion of this research is the improvement recommendations that is given to reduce the cause of failure of cutter of label machine cuts body label on the type of failure of the label sealer cutting process is not suitable with standard. The improvement step is to close the distance up between the conveyor and the conveyor table in the wrapping area.